Treatment of Recurrent Undifferentiated Pleomorphic Sarcoma of Infratemporal Fossa by Surgery Combined With Carbon Ion Radiotherapy: One Case Report - Wang, Zaixing; Tang, Zhiyuan; Zhao, Hailiang; Zeng, Xianhai; Han, Xiaodong; Zhang, Qiuhang (Frontiers in Surgery, 2021)
We retrospectively analyzed the diagnosis and treatment process of one patient with recurrent undifferentiated pleomorphic sarcoma (UPS) of infratemporal fossa and made a definite diagnosis by combining the imaging and pathological examination results. After treatment failure with 2 cycles of chemotherapy and several surgeries, UPS was eventually treated by surgery + carbon ion radiotherapy, and MRI reexamination showed no relapse. Head and neck UPS is located deeply, easily recurs after operation, and difficult to be resected completely by surgery, with a gradually shortened interval of relapse over the number of surgeries, which becomes a treatment challenge. After the last surgery, the patient received carbon ion radiotherapy, with a good therapeutic effect, and no sign of relapse just before sending this article. Based on the above advantages, we have concluded that surgery + carbon ion radiotherapy is a new effective pathway to treat head and neck UPS.